The FODMAP-Reducing Potential of Sourdough-Derived Lactobacillus Strains From the Marmara Region of Turkey - Sokmen, Ozen; Dundar, Ayse Neslihan; Bagci, Ufuk; Togay, Sine oezmen; Sahin, Oya Irmak; Saricaoglu, Furkan Turker (Wiley, 2025)
This study investigates the microbial diversity and FODMAP content of sourdough samples from Turkey's Marmara Region, collected in summer and winter. The primary objective was to identify lactic acid bacteria (LAB) strains capable of reducing FODMAP levels, which are associated with digestive disorders such as irritable bowel syndrome (IBS). The research was conducted in stages; in the first stage, sourdough samples were collected in different seasons and their FODMAP and fructan values were analyzed. In the second stage of the study, LAB strains were isolated from the sourdoughs with the lowest FODMAP and fructan levels, and new sourdough samples were prepared. A comprehensive analytical approach was undertaken, including FODMAP and fructan levels, fermentation characteristics, isolate identification, and chemical analysis of the samples. Among the tested samples, Bal & imath;kesir-1Y-1 significantly reduced fructan content by 48%, while Tejirda & gbreve;-1 K-2 and Edirne 1 K-2 exhibited the highest FODMAP reduction rates of approximately 64%. Additionally, Edirne-1 K-2 showed the strongest acidification potential, with 3.76 +/- 0.01 pH and 1.20% +/- 0.08% total titratable acidity, comparable with the control group. Seasonal variations significantly influenced microbial activity, with summer isolates demonstrating an enhanced enzymatic efficiency in FODMAP metabolism. The results highlight the potential of sourdough fermentation using targeted LAB strains to produce low-FODMAP foods that maintain high sensory and nutritional quality. This study highlights the significance of optimizing fermentation processes through targeted microbial selection and controlled conditions to achieve desirable nutritional and sensory attributes with dietary sensitivities.
Keywords: FODMAPs; irritable bowel syndrome (IBS); lactic acid bacteria (LAB); sourdough; yeast